Methods of inducing conditioned food aversion to Baccharis coridifolia (mio-mio) in cattle - Milton Begeres de Almeida (Ciência Rural, 2013)
Three experiments were performed to determine the efficacy of various methods of averting naïve cattle to prevent Baccharis coridifolia poisoning: forced oral administration of 0.5g kg-1 body weight of fresh B. coridifolia; forced inhalation of the smoke from burning B. coridifolia and rubbing the plant on the animals’ muzzles and mouths; and introducing the animals into paddocks with low invasion by B. coridifolia. Results demonstrated that cattle forced to ingest low doses become strongly averted if introduced into paddocks 23-26 hours after the aversion. In contrast, cattle introduced into the paddocks between 1-10 hours were not fully averted. Inhalation of B. coridifolia smoke, and rubbing the plant on the animals’ muzzles and mouths were not efficient to induce an aversion. The introduction of cattle into paddocks with approximately 1% of B. coridifolia was efficient if the animals remained 5 months in the area, but not if they only remained for 60 hours, as cattle required sufficient time to learn to avoid the plant.